AgGaS2 and Derivatives: Design, Synthesis, and Optical Properties - Guansheng Xing; Bing Chen (Nanomaterials)
Silver gallium sulfide (AgGaS2) is a ternary A(I)B(III)X(VI)2-type semiconductor featuring a direct bandgap and high chemical stability. Structurally resembling diamond, AgGaS2 has gained considerable attention as a highly promising material for nonlinear optical applications such as second harmonic generation and optical parametric oscillation. In attempts to expand the research scope, on the one hand, AgGaS2-derived bulk materials with similar diamond-like configurations have been investigated for the enhancement of nonlinear optics performance, especially the improvement of laser-induced damage thresholds and/or nonlinear coefficients; on the other hand, nanoscale AgGaS2 and its derivatives have been synthesized with sizes as low as the exciton Bohr radius for the realization of potential applications in the fields of optoelectronics and lighting. This review article focuses on recent advancements and future opportunities in the design of both bulk and nanocrystalline AgGaS2 and its derivatives, covering structural, electronic, and chemical aspects. By delving into the properties of AgGaS2 in bulk and nanocrystalline states, this review aims to deepen the understanding of chalcopyrite materials and maximize their utilization in photon conversion and beyond.